Building Customer Loyalty in Destination: A Case Study in Pelangi Island Jakarta - Ananta Budhi Danurdara; Aries Riswandi (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This dissertation aims to investigate the level of tourist's destination loyalty and satisfaction towards Pelangi Island. In addition, this study aims to reveal whether there is an influence between brand equity, tourist satisfaction, and decision making on customer loyalty. The results of this study are expected to be useful for managers in planning the development of appropriate tourism development strategies to increase customer loyalty. The research method used quantitative methods using a data collection tool in the form of an online survey questionnaire. In this study, the samples are people who like traveling especially to Thousand Islands, specifically Pelangi Island. The sampling technique used by the author to collect data is non-probability sampling with snowball sampling method and it has obtained 181 respondents. The data obtained were then analysed in form of tables, charts, and graphs. To conclude the study, the author presented the main findings based on the data that has been analysed. Some ideas were also recommended concerning developing the island's brand and product offering.